Identifikasi Potensi Bahaya dan Pengendalian Area Pengisian Galon Menggunakan Metode HIRA di PT. Taubah Jaya Abadi Kabupaten Berau, Kalimantan Timur - Anthonius Dhinar Hasto Wisnugroho; Fahriza Fawwas Asrory; Ramy Yahya; Selviana Ratna (Universitas Islam Raden Rahmat, Malang, 2024)
Increasingly tight competition in the Bottled Drinking Water management industry requires companies to optimize all resources in producing high-quality products, example PT. Taubah Jaya Abadi. Direct observations and interviews found potential dangers, including slipping, being crushed, and falling filled gallons. The research aims to determine the number of potential hazards and how to control them. The method used is Hazard Identification Risk Assessment (HIRA). The research subjects were 10 employees and the research object was potential danger. Results showed that there were 12 potential hazards with risk levels, namely low risk with 6 potential hazards (50%), moderate risk with 3 (25%), and high risk with 3 (25%). Improvement efforts for low risk include workers being required to use APD and installing slippery area signs; for moderate risk, namely moving equipment that is no longer in use, and for high risk, namely checking the gallon seal installation machine.